2016
DOI: 10.1016/j.ophtha.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Rate and Pattern of Rim Area Loss in Healthy and Progressing Glaucoma Eyes

Abstract: Objective To characterize the rate and pattern of age-related and glaucomatous neuroretinal rim area changes in subjects of African descent (AD) and European descent (ED). Design Prospective longitudinal study. Subjects 296 eyes of 157 healthy subjects (88 AD and 69 ED) and 73 progressing glaucoma eyes of 67 subjects (24 AD and 43 ED) from the Diagnostic Innovations in Glaucoma Study (DIGS) and the African Descent and Glaucoma Evaluation Study (ADAGES) were included. Methods Global and sectoral rim area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
(42 reference statements)
4
7
0
1
Order By: Relevance
“…27 Similarly, our group recently reported that longitudinal change in neuroretinal rim area (measured globally and by quadrant using confocal scanning laser ophthalmoscopy, CSLO) was similar over 5 years in AD and ED eyes with known progressive glaucomatous optic neuropathy (PGON; by masked stereoscopic photograph assessment) at study endpoint. 14 The current results are consistent with our previous results because PGON eyes in our previous report were glaucomatous at baseline with glaucomatous appearance of the optic nerve head or parapapillary retina in conjunction with repeatable abnormal VF results (i.e., eyes were similar to the eyes in our glaucoma group that showed no race-related differences). In addition, CSLO neuroretinal rim measurements are not comparable to SDOCT measurements because they are calculated using a standard reference plane placed 50 μm posterior to the optic disc margin along a user drawn contour line while SDOCT neuroretinal rim measurements, in the current study, were made relative to the BMO automatically identified based on z-axis a-scans.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…27 Similarly, our group recently reported that longitudinal change in neuroretinal rim area (measured globally and by quadrant using confocal scanning laser ophthalmoscopy, CSLO) was similar over 5 years in AD and ED eyes with known progressive glaucomatous optic neuropathy (PGON; by masked stereoscopic photograph assessment) at study endpoint. 14 The current results are consistent with our previous results because PGON eyes in our previous report were glaucomatous at baseline with glaucomatous appearance of the optic nerve head or parapapillary retina in conjunction with repeatable abnormal VF results (i.e., eyes were similar to the eyes in our glaucoma group that showed no race-related differences). In addition, CSLO neuroretinal rim measurements are not comparable to SDOCT measurements because they are calculated using a standard reference plane placed 50 μm posterior to the optic disc margin along a user drawn contour line while SDOCT neuroretinal rim measurements, in the current study, were made relative to the BMO automatically identified based on z-axis a-scans.…”
Section: Discussionsupporting
confidence: 93%
“…However, the rate of neuroretinal rim loss is similar between AD and ED eyes with glaucoma. 14 In addition, ADAGES results have demonstrated significant differences in optic disc morphology between healthy AD and ED groups including deeper confocal scanning laser ophthalmoscopy-measured cup depth, thinner optical coherence tomography (OCT)-measured macular thickness and thicker OCT-measured retinal nerve fiber layer (RNFL) in AD individuals, after controlling for differences in optic disc area between groups 15 (see also Girkin et al, Kashani et al, and Racette et al, 16-18 for similar OCT results and Tjon-Fo-Sang et al 19 for similar differences in scanning laser polarimetry-measured RNFLT). Differences in prevalence of glaucoma have been reported among regional AD populations 20 and subsequently, differences in RNFLT between races was shown to be marginally associated with biogeographic ancestry.…”
Section: Introductionmentioning
confidence: 99%
“…In the Baltimore study, similar results regarding increase in disc area were found although they were unable to find statistical significance [23]. Unlike previous studies such as the one performed by Hammel et al, our OCT measurements found an increase in rim area, which is unusual [24]. Taken together, these research findings may be useful for the development of prediction models which could utilize baseline structural change in newly-diagnosed OAG patients to determine whether patients are likely to progress, the rate at which they may progress, and if they require earlier intervention (i.e., pharmacologic, procedural, and/or operative) at the time of diagnosis.…”
Section: Plos Onesupporting
confidence: 46%
“…The ADAGES group characterized the rate and pattern of age-related and glaucomatous neuroretinal rim area changes in subjects of African and European descent, using HRT parameters. They showed that compared with healthy eyes, the mean rate of global rim area loss was 3.7 times faster and the mean rate of global percentage rim area loss was 5.4 times faster in progressing glaucoma eyes [50].…”
Section: Surrogate Endpoints and Progressionmentioning
confidence: 99%